Background frequency of Bacillus species at the Canberra Airport: A 12 month study. (December 2015) - Gahan, Michelle E.; Thomas, Rory; Rossi, Rebecca; Nelson, Michelle; Roffey, Paul; Richardson, Michelle M.; McNevin, Dennis
Highlights: 575 wipe samples collected from the Canberra Airport between August 2011–July 2012. Samples were screened for Bacillus species using real-time polymerase chain reaction. 2.4% (chromosome), 4.2% (pXO1) and 0.87% (pXO2) were positive for B. anthracis . 34% positive for B. thuringiensis with peaks October/November 2011 and April/May 2012. Provides a rapid method to screen for, and differentiate, Bacillus species. Abstract: Anthrax, caused by Bacillus anthracis, is a naturally occurring disease in Australia. Whilst mainly limited to livestock in grazing regions of Victoria and New South Wales, movement of people, stock and vehicles means B. anthracis could be present outside this region. Of particular interest is the "background" prevalence of B. anthracis at transport hubs including airports. The aim of this study was to determine the background frequency of B. anthracis and the commonly used hoax agent Bacillus thuringiensis at the Canberra Airport over a 12 month period. Samples were collected daily for seven days each month from August 2011–July 2012 and analyzed using species specific real-time polymerase chain reaction. Fourteen samples (of a total of 575) were positive for the B. anthracis PL3 genomic marker, 24 for the cya (pXO1) plasmid marker and five for the capB (pXO2) plasmid marker. Whilst five samples were positive for both PL3 and cya, no samples were positive for all three markers hence there is no evidence to suggest the presence of pathogenic B. anthracis strains. B. anthracis targets were detected primarily in February 2012 and B. thuringiensis peaked in October and November 2011 and again in April and May 2012. This study provides a rapid method to screen for, and differentiate, Bacillus species. Armed with this information investigators will be able to discriminate a "threat" from "background" frequencies should the need arise.